   Question Answers

# For any collection of n items, $\sum {\left( {x - \overline x } \right)}$A.$\sum x$B.$\overline x$C.$\text{n}\overline x$D.$0$  Verified
129k+ views
Hint:If the values of variables $x$ are ${x_1},{x_2},{x_3},.....,{x_n}$, where $'n'$ is the total number of values, then
Arithmetic mean $\left( {\overline x } \right)$
$\begin{gathered} = \dfrac{{{x_1} + {x_2} + {x_3} + ..... + {x_n}}}{n} = \dfrac{1}{n}\sum\limits_{i = 1}^{i = n} {{x_i}} \\ \\ \end{gathered}$
The symbol $\sum\limits_{i = 1}^{i = n} {{x_i}}$, denotes the sum ${x_1} + {x_2} + {x_3} + ..... + {x_n}.$
The arithmetic mean of a set of observations is equal to their sum divided by the total number of observations.

Let the total number of observations are ‘n’ and given, the mean of observation be $'x'$.
Then,
$\begin{gathered} \dfrac{{{x_1} + {x_2} + {x_3} + ..... + {x_n}}}{n} = x \\ \Rightarrow {x_1} + {x_2} + {x_3} + ..... + {x_n} = nx........(i) \\ \end{gathered}$
Then,

$\begin{gathered} \sum {\left( {x - \overline x } \right)} = \left[ {\left( {{x_1} - x} \right) + \left( {{x_2} - x} \right) + \left( {{x_3} - x} \right) + ...... + \left( {{x_n} - x} \right)} \right] \\ {\text{ = }}\left[ {\left( {{x_1} + {x_1} + {x_1} + ...... + {x_1}} \right) - \left( {x + x + x + .....n{\text{ times}}} \right)} \right] \\ \end{gathered}$
Since, from $\left( i \right)$ above, we have
${x_1} + {x_2} + {x_3} + ..... + {x_n} = nx$ and $x + x + x + ....... + x = nx$
Therefore,
$\sum {\left( {x - \overline x } \right)} = nx - nx = 0$

So, the correct answer is “Option D”.

Note:The arithmetic mean of a set of observations is equal to their sum divided by the total number of observations.
$\begin{gathered} \dfrac{{{x_1} + {x_2} + {x_3} + ..... + {x_n}}}{n} = x \\ \Rightarrow {x_1} + {x_2} + {x_3} + ..... + {x_n} = nx \\ \end{gathered}$
And also,
$x + x + x + ....... + x = nx$.